INDONESIA'S MARITIME DIPLOMACY (CASE STUDY: MARITIME TERRORISM IN THE SULU-SULAWESI SEAS) - Haikal, Muhammad; Wahyudin, Y. A.; Mahmuluddin (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
Maritime terrorism is an activity that involves illegal actions that directly or indirectly impact a country's interests at sea. These actions include piracy, robbery, assault, and illegal trafficking in weapons, people and drugs. Maritime terrorism does not always have political aims, but has other aims, namely economic. The Sulu-Sulawesi Sea is a region in southeast asia that frequently affected by maritime terrorism. As maritime country, Indonesia has responsibility to protect the security of its maritime territory and must collaborate with neighboring countries to do so. This paper employs the concept of maritime diplomacy to examine the measures Indonesia has implemented in the region. The results of various forms of maritime diplomacy efforts made by Indonesia have succeeded in reducing maritime terrorism activities in the Sulu-Sulawesi sea area from time to time.